Update Breast Cancer 2019 part 4: diagnostic and therapeutic challenges of new, personalised therapies for patients with early breast cancer = Update Mammakarzinom 2019 Teil 4 : diagnostische und therapeutische Herausforderungen neuer personalisierter Therapien für Patientinnen mit frühem Mammakarzinom - Schütz, Florian; Wallwiener, Markus; Schneeweiss, Andreas (Geburtshilfe und Frauenheilkunde, 2019)
The further development of therapies for women with early breast cancer is progressing far more slowly than in the case of patients with advanced breast cancer and is additionally delayed compared to developments in metastatic breast cancer. Nonetheless, significant advancements have been able to be recorded recently. This review summarises the latest developments in view of the most recent publications and professional conferences. For hormone-receptor-positive patients, new aspects for the duration of antihormone therapy and with regard to the benefits of multigene tests have been published. In the case of HER2-positive patients, the value of post-neoadjuvant therapy and de-escalation of the therapy is discussed. In patients with triple-negative breast cancer, there is a question of whether the knowledge of the biological background of a homologous recombination deficiency (HRD) helps develop new therapies for this subtype. In particular the “use” of a BRCA1/2 mutation or the biological characteristic HRD as a potential motive for therapy plays a role here in specifying the significance of platinum therapy and therapy with PARP inhibitors.
Gesehen am 05.05.2020